Studi Komparasi Hasil Belajar Fiqih Antara Model Pembelajaran Kooperatif Tipe Group Investigation dan Model Pembelajaran Konvensional Siswa Kelas XI MA Al-Ihsan Kalikejambon Jombang - Izzah, Siti Laylatul; Priyono, Ali; Lilawati, Emi (Universitas KH. A. Wahab Hasbullah, 2021)
ABSTRACT Comparative Study of Jurisprudence Learning Outcomes Between Cooperative Learning Model Type Group Investigation and Conventional Learning Model Class XI Students MA Al - Ihsan Kalikejambon Jombang. The purpose of this study was to determine the difference in learning outcomes between the cooperative learning model type Group Investigation and the conventional learning methods of class XI MA Al-Ihsan Kalikejambon Jombang. This research uses a quantitative research approach with the type of experimental research in order to find differences in the learning outcomes of the experimental and control groups after a certain treatment has been given to others under controlled conditions. Based on the results of statistical calculations from the average post-test results of the experimental class 90.00 and the average post-test results of the control class 79.44, the calculation was obtained using the SPSS 25.00 for windows program with a significance (Sig 2-tailed) of 0.002. Because the Sig. (2 - tailed) is less than 0.05 (0.002 <0.05) then Ha is accepted. Thus it can be concluded that there is a significant difference between the post-test results of the experimental class and the control class. Thus, it can be said that the teaching and learning process carried out with the group investigation type cooperative learning model in class XI MIPA was better than the conventional learning model in class XI IIS on student learning outcomes in Islamic Civilization History subjects.